Performance Assessment of Cassava Peel Starch and Alum as Dual Coagulant for Turbidity Removal in Dam Water - Mohd Asharuddin, Syazwani; Othman, Norzila; Mohd Zin, Nur Shaylinda; Tajarudin, Husnul Azan; Md. Din, Mohd Fadhil (International Journal of Integrated Engineering, 2018)
The agricultural and food processing industries generate a significant portion of residues, refuse and waste. Conversion of these wastes into useful end product would be beneficial not only to the economy but also the environment as it reducing the solid waste disposal problem. The present study was aimed to investigate the performance of cassava peel starch (CPS) extracted from cassava peel waste in combination with alum to act as dual coagulant for turbidity removal in raw water from Sembrong dam. Comparative studies by employing both alum and CPS as primary coagulant using several series of Jar test were also conducted. Results showed that the usage of alum-CPS as dual coagulant not only enhanced the turbidity removal with maximum achievement up to 91.47%, but also significantly improve the coagulation process by reducing both alum dosage and settling time up to 50% which indicates broad prospects to be further developed as emerging green coagulant.